EFEKTIVITAS COKLAT KELOR TERHADAP KEJADIAN DISMINORE: - Yuliyanik (Media Husada Journal of Midwifery Science, 2025)
Dysmenorrhea is a pain disorder experienced by women during menstruation. Menstrual pain can interfere with daily activities if not handled properly. There are two types of dysmenorrhea, namely primary dysmenorrhea and secondary dysmenorrhea. Dysmenorrhea that often occurs is primary dysmenorrhea, while secondary dysmenorrhea is dysmenorrhea experienced by a woman with indications of a disease. Menstrual pain which is included in primary dysmenorrhea can be overcome by consuming natural preparations, namely chocolate. This statement is in accordance with research that has been done that there is a relationship between consuming chocolate and the incidence of dysmenorrhea. This research will be carried out by giving moringa chocolate preparations to the incidence of dysmenorrhea. The study population was female students at MTS Al Munawwaroh, Jambu Village, Pandanmulyo Hamlet, Kec.Tajinan, Kab. Malang as many as 40 female students. Sampling according to the inclusion criteria. The research time is June 2023. The research location is at MTS Al Munawwaroh, Jambu Village, Pandanmulyo, Kec.Tajinan, Kab. Malang. Data was collected by giving questionnaires and the data was processed using SPSS 26. The purpose of this study was to determine the effectiveness of moringa chocolate on the incidence of dysmenorrhea. The results and conclusions answer the research that has been done.